PERLINDUNGAN HUKUM TERHADAP PEMEGANG MEREK TERKENAL FARMSTAY UNTUK KELAS SEJENIS - Raharjo, Muhammad Hidayattullah; Bustani, Simona (Tribuere, 2023)
Disputes against well-known brands often occur in Indonesia. One of them is in the case of the Central Jakarta Commercial Court decision Number 70/PDT.SUS-MEREK/2022/PNNIAGA JKTPST. The issues raised are 1) what is the legal protection for holders of well-known farmstay brands for similar classes based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications and 2) what are the judge's considerations in Decision Number 70/PDT.SUS-MEREK/2022/PN NIAGA JKT PST is seen from Law Number 20 of 2016 concerning Marks and Geographical Indications. The research method is of the normative type with the nature of descriptive research, the data used is secondary data which is carried out through literature study and then qualitative analysis and deductive logic are carried out to draw conclusions. From the results of the research, it can be seen that legal protection for holders of well-known farmstay brands for similar classes is by granting an application to be able to apply for cancellation of a brand, in this case the trademark registration was carried out by Monica based on Article 21 paragraph (1) letter b and paragraph (3) Law on Trademarks and Geographical Indications. The judge, in his legal considerations, rejected the application for cancellation of a trademark, which was not in accordance with the provisions of Article 21 paragraph (1) letter b and paragraph (3) of the Trademark Law, which is the reason a registered mark can be canceled as contained in the provisions of Article 76 paragraph (1) of the Law. -Law on Trademarks and Geographical Indications.